1994
DOI: 10.1002/poc.610070607
|View full text |Cite
|
Sign up to set email alerts
|

Hydride transfer reactions of Michler's hydride with different π‐accetors

Abstract: The hydride transfer reactions of 4,4′‐bis(dimethylaminophenyl)methane (Michler's hydride) with p‐benzoquinones were studied. The rate of formation of Michler's Hydrol Blue was followed spectrophotometrically. The second‐order rate constants and the activation parameters were estimated. The formation of a charge‐transfer complex was observed at low temperatures. Stable and unstable paramagnetic species formed during the reactions were assigned by ESR spectroscopy. The observed kinetic behaviour and the stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Since leucomethylene blue (MBH) and leucothionine (TH) are very unstable and easily oxidized by co-existing oxygen in solution, few kinetic studies on the reactions of these compounds with p-acceptors have been reported. Recently, we have studied the kinetics of the reactions of TH and MBH with two-electron oxidants by producing TH and MBH in a closed system by photoreductions of thionine (T ) and methylene blue (MB ) with triethylamine.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Since leucomethylene blue (MBH) and leucothionine (TH) are very unstable and easily oxidized by co-existing oxygen in solution, few kinetic studies on the reactions of these compounds with p-acceptors have been reported. Recently, we have studied the kinetics of the reactions of TH and MBH with two-electron oxidants by producing TH and MBH in a closed system by photoreductions of thionine (T ) and methylene blue (MB ) with triethylamine.…”
Section: Introductionmentioning
confidence: 99%